Reviewer Acknowledgements for Business and Economic Research, Vol. 13, No. 1 - Young, Daisy (Business and Economic Research, 2023)
<div class="WordSection1" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> Business and Economic Research (BER) would like to thank the following reviewers for reviewing manuscripts from January 1, 2023, to March 1, 2023. Their comments and suggestions were of great help to the authors in improving the quality of their papers. Many authors, regardless of whether BER publishes their work, appreciate the helpful feedback provided by the reviewers. Macrothink Publishing appreciates the following reviewers’ rigorous and conscientious efforts for this journal. Each of the reviewers listed below returned at least one review during this period. <div class="WordSection2" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> Abeer M. Ali Abd Elkhalek Ahmed Zouhair Almir A. Alihodžić Bratu (Simionescu) Mihaela Cosimo Magazzino Cristina Alina Naftanaila Elena Gurgu Fayez Bassam Shriedeh Hengky Sumisto Halim José Martins Kimty Seng Mamta Singh Mohsen Mohaghegh Muddassar Sarfraz Nemer Badwan Oleksandr V. Dluhopolskyi Rabeya Khatoon Roderikus Agus Trihatmoko Romeo Victor Ionescu Santosh B. Manjegowda Shyamkumar D. Kalpande Yixun Xing Zi-Yi Guo